Nascent chains can form co-translational folding intermediates that promote post-translational folding outcomes in a disease-causing protein - Elena Plessa (Nature Portfolio, 2021)
Alpha-1-antitrypsin (AAT) deficiency results from misfolding-prone AAT variants. Here the authors show that AAT forms co-translational folding intermediates on the ribosome that persist upon release and determine its folding fate. They show too that the ribosome can also modulate misfolding-prone AAT intermediates during their synthesis.